A comparative study of tetraethylammonium hydroxide polymer electrolytes for solid electrochemical capacitors. (2nd September 2016) - Li, Jak; Lian, Keryn
Abstract: Hydroxide (OH − ion)-conducting polymer electrolytes are essential for enabling cost effective, solid-state energy storage devices such as electrochemical capacitors (ECs). Ultra-high rate ECs using OH − ion-conducting polymer electrolytes have been developed and characterized. These polymer electrolytes comprised of aqueous tetraethylammonium hydroxide (TEAOH) incorporated into poly(vinyl alcohol) (TEAOH-PVA), poly(ethylene oxide) (TEAOH-PEO), or poly(acrylic acid) (TEAOH-PAA). Solid EC cells enabled by TEAOH-PVA, TEOAH-PEO, and TEAOH-PAA were characterized by electrochemical impedance spectroscopy and cyclic voltammetry under ambient conditions, demonstrating clear differences in performance. Through XRD and DSC analyses, the effects of the polymer hosts on the OH − ion-transport mechanism was revealed. The differences in OH − ion-transport in the polymer electrolytes is likely a result of differences in crystallinity, hydrophilicity, and functional group electronegativity of the polymer hosts. TEAOH-PVA and TEAOH-PAA based solid EC cells achieved an ionic conductivity of 5 mS cm −1 and an ultra-high rate of 5000 V s −1 making them suitable for EC applications. Graphical abstract: Highlights: Three OH − ion conducting polymer electrolytes were developed and compared. Tetraethylammonium hydroxide (TEAOH) was used as the ionic conductor. Effects of crystallinity and hydration on OH − ion conduction were proposed. Polymer functional groups interacted selectively with the ionic conductor. A stable ionic conductivities of 5 mS cm −1 at ambient conditions were achieved.